Taxonomic revision of Saffron-billed Sparrow Arremon flavirostris Swainson, 1838 (Aves: Passerellidae) with comments on its holotype and type locality - Buainain, Nelson; Brito, Guilherme Renzo Rocha; Firme, Daniel Honorato; Figueira, Daniel Monteiro; Raposo, Marcos A.; de Assis, Claydson Pinto (Zootaxa, 2016)
The Saffron-billed Sparrow (Arremon flavirostris) complex occurs in the undergrowth of deciduous woodlands and forests from the Andes of Bolivia and northern Argentina to Paraguay and southern, mid-western and interior eastern Brazil. Currently four subspecies are recognized: A. f. flavirostris, A. f. polionotus, A. f. devillii and A. f. dorbignii. We review the taxonomy of this complex by analyzing coloration and morphometrics of a series of 234 skins, and by comparing 101 sound recordings. Our results suggest that under both the Phylogenetic and Biological Species Concept, three species should be recognized in this complex: A. flavirostris, A. polionotus and A. dorbignii. On the other hand, A. devillii should be considered a junior synonym of A. polionotus since these two have no constant differences in morphology and vocalization. These species are diagnosable by their coloration characters, but not by morphometrics. Vocalizations are useful in diagnosing A. flavirostris from A. dorbignii, but do not diagnose A. polionotus from the others. We show that part of the previous taxonomic confusion can be attributed to variation in back color of adult and immature A. polionotus. Finally, we comment on the recently located holotype of A. flavirostris, which was believed to be lost, and its type locality.